Conectando Saberes: possíveis diálogos entre conhecimentos científicos e tradicionais - Ferraz, Vasty Veruska Rodrigues. (2023)
Pedagogical practices permeate the entire school environment and are extremely important to achieve the objectives proposed by the teaching and learning process, they organize the work of teachers and help to enhance learning. Pedagogical practices are not neutral, they are impregnated with intentions and are great allies of emancipatory education, which aims to build critical subjects, who understand, reveal the reality in which they are immersed and seek ways to build a more inclusive, fair and egalitarian society for everyone. The work presented is a qualitative bibliographical research that aims to analyze, through scientific articles, how pedagogical practices developed in different places in Brazil that adopted the traditional knowledge of a certain human group to articulate a scientific school education, supported by the teachings by Paulo Freire. The articles were captured on the Google Scholar platform to be examined and so that we could identify, recognize and describe the traditional knowledge that contributed to a school scientific education, what were the difficulties and possibilities encountered to carry out the pedagogical practices and what type of practice helped to favor learning. Paulo Freire is the theoretical framework of the research, and the data will be analyzed in the light of Freire's pedagogy and the theoretical references adopted. Only 6 articles related to the theme have internal consistency, present congruent results to the research proposal, present a good argument, reasoning logic, coherence between the research question, objectives and conclusions. The 6 articles do not contradict each other, they do not expose elements that can be refuted, but data that prove the results. The articles contributed to thinking about a scientific education articulated with different traditional knowledge, such as: indigenous, from the Geraizeira community, from the rural community and from the peasant community. The pedagogical practices described are possible to be carried out with the students, they occurred in different places of the national territory, with different peoples and ethnic groups, making explicit the cultural diversity of Brazil. The intention of the research was to demonstrate that it is favorable to the teaching and learning process, to adopt pedagogical practices that connect the traditional knowledge of the community where the school or university is inserted, with the school scientific knowledge. The intention of the investigation was also to expose that considering the reading of the world of the students, their knowledge of experience made and contextualizing school education, enhances learning.